The Perception of English Study Program Students on Using TikTok Videos for Learning Pronunciation - Reza Asra Maulana; Eliwarti Eliwarti; Indah Tri Purwanti (FKIP - Universitas Riau, 2026)
This study aimed to find out the perceptions of English Education Study Program students about using TikTok videos for learning English pronunciation. Pronunciation is an important component of speaking skills, but students often have limited exposure to authentic pronunciation. As TikTok is becoming increasingly popular, this application can be used to learn through short videos. This study used a mixed-method design, starting with quantitative data collection, followed by qualitative data collection. The quantitative data was collected from a questionnaire given to 70 fifth-semester students from the English Education Study Program, Faculty of Teacher Training and Education, Universitas Riau. Qualitative data was obtained from interviews with eight selected individuals. The results showed that students had positive perceptions about using TikTok to learn pronunciation. They considered TikTok to be easy to use, fun, and useful for learning English pronunciation. Additionally, students showed a positive attitude and willing to continue using TikTok, although many see it as only an additional tool, not the main one. To wrap up, TikTok can be a good tool for learning pronunciation if used correctly when learning English.